What influences adherence to guidance for postoperative instillation of intravesical chemotherapy to patients with bladder cancer?. (28th March 2021) - Dunsmore, Jennifer; Duncan, Eilidh; Mariappan, Paramananthan; de Bruin, Marijn; MacLennan, Sara; Dimitropoulos, Konstantinos; Kasivisvanathan, Veeru; Mostafid, Hugh; Briganti, Alberto; N'Dow, James; MacLennan, Steven
Abstract : Objective: To understand the barriers and facilitators to single instillation of intravesical chemotherapy (SI‐IVC) use after resection of non‐muscle‐invasive bladder cancer (NMIBC) in Scotland and England using a behavioural theory‐informed approach. Subjects and Methods: In a cross‐sectional descriptive study of practices at seven hospitals, we investigated care pathways, policies, and interviewed 30 urology staff responsible for SI‐IVC. We used the Theoretical Domains Framework (TDF) to organise our investigation and conducted deductive thematic analyses, while inductively coding emergent beliefs. Results: Barriers to SI‐IVC were present at different organisational levels and professional roles. In four hospitals, there was a policy to not instil SI‐IVC in theatre. Six hospitals' staff reported delays in mitomycin C (MMC) ordering and/or local storage. Lack of training, skills and perceived workload affected motivation. Facilitators included access to modern instilling devices (four hospitals) and incorporating reminders in operation proforma (four hospitals). Performance targets (with audit and feedback) within a national governance framework were present in Scotland but not England. Differences in coordinated leadership, sharing best practices, and disliking being perceived as underperforming, were evident in Scotland. Conclusions: High‐certainty evidence shows that SI‐IVC, such as MMC, after NMIBC resection reduces recurrences. This evidence underpins international guidance. The number of eligible patients receiving SI‐IVC is variable indicating suboptimal practice. Improving SI‐IVC adherence requires modifications to theatre instilling policies, delivery and storage of MMC, staff training, and documentation. Centralising care, with bladder cancer expert leadership and best practices sharing with performance targets, likely led to improvements in Scotland. National quality improvement, incorporating audit and feedback, with additional implementation strategies targeted to professional role could improve adherence and patient outcomes elsewhere. This process should be controlled to clarify implementation intervention effectiveness.